Integrating livestock, trees and crops - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
A pilot project in Nigeria, combining traditional crops with trees (Leucanea leucocephala and Gliricidia sepium) that are grown for livestock grazing, appears to be succeeding. The project began in 1984 with 60 small producers and has been expanded...